1994
DOI: 10.2135/cropsci1994.0011183x003400010021x
|View full text |Cite
|
Sign up to set email alerts
|

Remobilization of Carbon and Nitrogen in Wheat as Influenced by Postanthesis Water Deficits

Abstract: Preanthesis stored C and N in wheat (Triticum aestivum L.) are important in a mediterranean climate because grain filling frequently depends on the remobilization of preanthesis assimilates. We determined the effect of the rate of development of postanthesis water deficits on the remobilization of C and N to the grain using stable isotopes of C and N accumulated in the plant during the vegetative phase. Plants were grown in pots with adequate water and under similar temperature and humidity conditions until an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
140
0
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(159 citation statements)
references
References 0 publications
13
140
0
6
Order By: Relevance
“…In fact, plant dry matter was the same across treatments until heading, when spikes differed in dry weight. Grain filling and partitioning of assimilates to developing grains are usually affected by post-anthesis water deficit (Broklehurst, 1978;Kobata et al, 1992;Palta et al, 1994). Plants amended with split applications of soil N showed relatively lower 1000-seed weight, probably for the greater number of kernels per spike with respect to other treatments.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, plant dry matter was the same across treatments until heading, when spikes differed in dry weight. Grain filling and partitioning of assimilates to developing grains are usually affected by post-anthesis water deficit (Broklehurst, 1978;Kobata et al, 1992;Palta et al, 1994). Plants amended with split applications of soil N showed relatively lower 1000-seed weight, probably for the greater number of kernels per spike with respect to other treatments.…”
Section: Resultsmentioning
confidence: 99%
“…In traits like TDM, RDM and LAI, drought reduced the days to reach the maximum peak. Extensive studies have demonstrated that water deficits result in early senescence (Kobata et al 1992, Palta et al 1994, Zhang et al 1998). Many factors contribute toward early senescence (Lers et al 1998, Nooden 1988), but ABA is considered the most promising of the early senescence promoters (Nooden 1988, Madhu et al 1999, Tadas et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Embora o ajustamento osmótico não impeça que a taxa fotossintética seja reduzida sob condições de estresse hídrico (Jones & Rawson 1979), a manutenção da turgescência permite que a fotossíntese e outras importantes atividades fisiológicas sejam mantidas, mesmo que baixas, possibilitando a redistribuição de carbono e nitrogênio (Kobata et al 1992, Palta et al 1994.…”
Section: Introductionunclassified